2010
DOI: 10.2144/000113445
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized FISH for Screening of Onco-Hematological Malignancies

Abstract: Fluorescence in situ hybridization (FISH) represents a major step in the analysis of chromosomal aberrations in cancer. It allows the precise detection of specific rearrangements, both for diagnostic and prognostic purposes. Here we present a miniaturized FISH method performed on fresh and fixed hematological samples. This procedure has been developed together with a microfluidic device that integrates cluster-assembled nanostructured TiO2 (ns-TiO2) as a nanomaterial promoting hematopoietic cell immobilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…Liu et al 13 reported modification of a glass surface with (3-aminopropyl) triethoxysilane (APTES) and polyethylene glycol (PEG)-silane for fabrication of a cell array. To promote cell attachment, Zanardi et al 14 performed surface coating with TiO2 nanoparticles.…”
Section: ·2 Materialsmentioning
confidence: 99%
“…Liu et al 13 reported modification of a glass surface with (3-aminopropyl) triethoxysilane (APTES) and polyethylene glycol (PEG)-silane for fabrication of a cell array. To promote cell attachment, Zanardi et al 14 performed surface coating with TiO2 nanoparticles.…”
Section: ·2 Materialsmentioning
confidence: 99%
“…The most recent example of an interphase FISH on chip was presented by Zanardi et al, (2010). They presented a miniaturization of the interphase FISH protocol through microfluidic methods with minimized shear stress exerted on cells (living or fixed) during sample loading.…”
Section: Miniaturized Interphase Fishmentioning
confidence: 99%
“…There has been few reports on performing cytogenetic analysis using microfabricated devices [6][7][8][9][10][11][12][13][14][15]. They offer a reduction in the reagents volume with great focus on minimizing the amount of the DNA probe used.…”
Section: Introductionmentioning
confidence: 99%